Exploring the dynamic link between FDI, remittances, and ecological footprint in Pakistan: Evidence from partial and multiple wavelet based-analysis - Muhammad Zubair Chishti (Research in Globalization, 2023)
The current study aims at studying the asymmetric nexus between foreign direct investment (FDI), foreign remittances inflow (RMIT), and ecological footprint (EF) for Pakistan from 1976Q1-2020Q4. To this end, our article deploys Morlet’s wavelet method. Simply, the recent paper employs Wavelet Coherence Transform (WCT), Partial and Multiple Wavelet Coherence (PWC & MWC) to divulge the dynamic nexus among the series under study. With respect to frequency and time domains, the significant wavelet coherence and robust lead-lag association are inferred. Furthermore, FDI exhibits a strong co-movement with EF, implying that variations in the FDI inflows are highly sensitive to the environment. Likewise, RMIT demonstrates a significant association with EF. Besides, the frequency domain causality test validates our findings by confirming the causal links of FDI and RMIT with EF. Based on the results, some salient policies are suggested to tackle the exigency of environmental pollution.